1990
DOI: 10.1080/01635589009514101
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of snuff, retinoic acid, andß‐carotene on DMBA‐induced hamster cheek pouch carcinogenesis in relation to keratin expression

Abstract: The hamster cheek pouch (HCP) serves as an excellent model system not only for the studies on initiation and promotion but also for the modulation of experimental oral carcinogenesis. In our studies, HCPs treated with 7,12-dimethylbenz[a]anthracene (DMBA) showed both cheek pouch and stomach papillomas. Utilizing this model system, we tested and compared the modulatory effects of snuff, retinoic acid, and beta-carotene on the incidence of tumors and the keratin expression pattern. HCPs treated with snuff, eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…[75] However, in another study, forestomach tumors developed the following application of snuff to the hamster cheek pouch mucosa. [76] Skin papillomas were induced following application of black or brown masheri extract to the back skin of nude Swiss mice, [63] although topical application of a black masheri extract did not induce skin tumors in Swiss mice. Similar treatment, however, resulted in skin papilloma development in hairless Swiss mice and the extract promoted skin papilloma formation in DMBA initiated Swiss mice.…”
Section: Carcinogenicity Of Sltmentioning
confidence: 99%
“…[75] However, in another study, forestomach tumors developed the following application of snuff to the hamster cheek pouch mucosa. [76] Skin papillomas were induced following application of black or brown masheri extract to the back skin of nude Swiss mice, [63] although topical application of a black masheri extract did not induce skin tumors in Swiss mice. Similar treatment, however, resulted in skin papilloma development in hairless Swiss mice and the extract promoted skin papilloma formation in DMBA initiated Swiss mice.…”
Section: Carcinogenicity Of Sltmentioning
confidence: 99%
“…Ten studies on OC showed that vitamin A supplementation, oral or injected, significantly reduced the lesion size progression and tumour count, with signs of total inhibition of carcinogenesis in the hamster cheek pouch model [37]. Notably, one study reported that topical vitamin A treatment resulted in oral leukoplakia progressing to OSCC in the hamster buccal pouch model [38].…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
“…Outros estudos têm evidenciado ação protetora do β-caroteno contra carcinogênese conduzida em animais, em associação a determinados nutrientes. Nesse sentido, ALABASTER et al (1995) CHEN et al (1993) NISHINO (1995) SUDA et al (1986) GIJARE et al (1990) MORENO et al (1991e 1995a SARKAR et al…”
Section: Estudos Em Animais (In Vivo)unclassified